Experimental Study on Type I Fracture Toughness and Compressive Strength of Compacted Clay - LIU Hui; JIN Songyang; ZHANG Haoyu (Renmin Zhujiang)
Whether in engineering or in nature, clay is mostly under compression, which is commonlysuffered with shear compression failure. Therefore, the research on the type I fracture toughnessand compressive strength of compacted clay is of great significance to the engineering structuredesign. This paper tests the compacted clay under different water content conditions throughunconfined compressive strength test and improved three-point bending test. The results show that:In the three-point bending test, the prefabricated crack length of the compacted clay needs tobe controlled at 15 to 30 mm to truly reflect the type I fracture toughness of the soil; Thetype I fracture toughness and unconfined compressive strength of the compacted clay both increasefirst and then decrease with the increase of the water content, so the compacted soil can maximizeits compression and fracture resistance when it is constructed at the optimal moisture content;Under different water content conditions, the type I fracture toughness and unconfined compressivestrength of compacted soil have a good linear correlation.